Síntese de microfibras biopoliméricas de zeína/hidroxipropilmetilcelulose e nanofibrila para liberação controlada de fármacos - Ferreira, João Otávio (Universidade Federal de São Carlos, 2022)
This master’s thesis aimed to develop electrospun microfibers formed by hydroxypropylcellulose acetate succinate (HPMC-AS), zein and celulose nanofibril to be used in the release of metronidazole (MDZ) and metronidazole benzoate (BMDZ), which are important drugs in the treatment of periodontal disease. The morphology, chemical composition and cristalinity of the membranes were analyzed by scanning electron microscopy (SEM), infrared (FTIR) and X-ray diffraction (XRD), respectively. The termal behavior of the fibers was investigated by differential scanning calorimetry (DSC) and thermogravimetry (TGA). Furthermore, the drug release profile and the kinetic mechanism were also evaluated. The results showed that microfibers were produced without defects, amorphous and with average diameters of 1,689; 1,298 and 1,395μm mμ for membranes formed by HPMC-AS/zein in the proportion of 40/60, 50/50 and 60/40 (% w/w), respectively. Microfibers formed by HPMC-AS/zein 60/40 presented the smallest average diameter and fewer defects on their surface, which is the reason this system was chosen for drug delivery purposes. However, after addition of the drugs, extensive crystallization of the drugs was visualized on the fiber surface and also many deffects were produced. Thus, celulose nanofibrils were added to this system, producing defect-free and semi-crystalline fibers with an average diameter of 1,968; 1,076 and 1,510μm for systems containing 20% MDZ / 20% BMDZ, 40% MDZ and 40% BMDZ, respectively. FTIR, XRD and DSC results suggested intermolecular interactions via hydrogen bonding among polymeric chains and the drugs, with a decrease in the melting temperature of the drug crystals present in the fibers. Drug release profile from fibers containing 40% of each drug showed a fast release of MDZ molecules in the first 6h (80%), while BMDZ showed a slower release (30%). For the membrane containing 20% of each drug, the drug release decreased with maintenance of 55% for at least 5 days, concomitantly with suficiente therapeutic amounts of the drugs in the first hours (40%). In other words, electrospun fibers of HPMC-AS, zein and cellulose nanofibril containing metronidazole and metronidazole benzoate are strategic materials that provides na immediate release of the drugs for the initial treatment of periodontitis and a slow release for the maintenance of drugs in the oral tract for hours/days.
Synthesis of zein/hydroxypropylmethylcellulose and nanofibril biopolymer microfibers for controlled drug delivery
Keywords: Eletrofiação; Microfibras; Hidroxipropilcelulose acetato succinato; Zeína; Nanofibrila de celulose; Metronidazol e benzoato de metronidazol; Electrospinning; Microfibers; Hydroxypropyl Cellulose Acetate Succinate; Zein; Cellulose nanofibril; Metronidazole and Metronidazole Benzoate; CIENCIAS EXATAS E DA TERRA::QUIMICA